(untitled) - Meyer, Thierry (Weinheim, 2005)
This first book dedicated to all aspects of the field presents our current knowledge in its entirety, covering the necessary disciplines and processes involved - from the monomer to the final product. With an international editor and author team from academia and such leading chemical companies as Bayer, BASF and DuPont, the text adopts a multidisciplinary approach and a practical point of view. Starting with polymer chemistry and thermodynamics, the book goes on to deal with measurement, control, and characterization, before tackling process development, safety issues, scale-up, and modeling. It concludes with emerging processes.
Keywords: Polymerization; Congresses